The Potential Psychological Advantages of the Focusing-Oriented Therapy: A Pilot Quasiexperimental Study of “Proficiency as Focusing Partner” Training Workshop on Self-Compassion - Ming Yu Claudia Wong (International Journal of Clinical Practice)
Results and Conclusion: This pilot study addresses the lack of research on focusing therapy training workshops for the general population. The findings suggest that the “Proficiency in Focusing Partnership” training workshop can significantly improve self-compassion, mainly by reducing negative self-compassion. However, further development of evidence-based focusing-oriented interventions is needed.